Social inequality as a vector of homicides in the States of São Paulo, Brazil (Research, Society and Development, 2021)
Violence is one of the sad realities experienced in urban areas of the State of São Paulo. One of the questions that is tried to answer when there is an act of violence, for example homicide, is related to the causes that influenced these acts. Thus, the present work sought to define a statistical model that allows a precise description of homicide cases in the State of São Paulo, taking into account some socio-demographic indicators resulting from the 2000 census. Three scenarios of the Poisson distribution model and four scenarios of the negative binomial distribution, were adjusted. Through the Akaike Information Criterion, the model of negative binomial responses was identified as the best model for modeling homicide cases in the state, and it was found that socio-economic inequality significantly contributes to the occurrence of homicide cases in the State of São Paulo.